Entrapment - Amin Babjee, Shaikh Mohamed (Universiti Putra Malaysia Press, 2015)
Various trapping methods have been used by the Malay villagers and Orang Asli to trap animals in Peninsular Malaysia. For entrapment of wild and extremely sensitive red jungle fowl, the talents of an informed trapper who will use his aqcuired knowledge on the behaviour and sensitivity of wild birds, and the quality of decoys are important. A decoy (denak) is a living, trained cross-bred jungle fowl that is used to attract and challenge the wild dominant male jungle fowl in its own natural territory. The quality of a decoy is mainly based on the quality and type of crow, the appearance and behavioural expression of the challenging behaviors, during the response and approach of the wild male subject.